Quantifying fundamental movement skills during active video games - Thornton, A.; Lay, B.; Rosenberg, M.; Granich, J.; Braham, R. (Journal of Motor Learning and Development, 2014)
This study sought to explore the type of fundamental movement skills (FMS) performed during Active Video Game (AVG) play, as well as the frequency with which these FMS are performed. In addition, this study aimed to determine the relationship between FMS performance and energy expenditure during 15 min of AVG play across two Microsoft Xbox Kinect AVGs. Fundamental movement skills were observed via video by two raters and energy expenditure derived using Actiheart monitors in children aged 10-15 years. Six different FMS were observed during AVG play with differences in the number of FMS performed between the two AVGs. The overall energy expended (Joules/kg/minute), however, was similar between the AVGs, suggesting the frequency of FMS did not influence overall energy expended during play. The movements observed during AVG play that possibly accounted for the energy expenditure, were not of a quality that could be classified as FMS. This research demonstrates that children playing these two games have the opportunity to repeatedly perform mostly two FMS, namely jumping and dodging. The goal of the AVGs, however, could be achieved with generalized movements that did not always meet the criteria to be classified as a FMS.